2019
DOI: 10.1016/j.jad.2019.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Affective interference in borderline personality disorder: The lethality of suicidal behavior predicts functional brain profiles

Abstract: Background.-Negative affective interference with executive cognition is associated with emotion dysregulation and behavioral dyscontrol in BPD, including a diathesis to suicidal and self-injurious behavior. While clinically well described, the neural basis of affective interference with central executive network function, and resulting suicidal behavior is poorly understood. Method.-In an fMRI study, 23 BPD suicide attempters completed an affectively modified Continuous Performance Task(X-CPT), in which target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 92 publications
(110 reference statements)
0
8
0
1
Order By: Relevance
“…Normative studies of brain function In experimental contexts, both positive and negative valence hold substantial salience in the typical human brain and underpin brain networks that drive social interactions (Nummenmaa et al, 2012). However, whereas positively valenced stimuli are 'preferred' in healthy controls (Nielen et al, 2009;Winecoff et al, 2013), negatively valenced stimuli are more salient to patients with BPD (Soloff et al, 2015;Soloff, Chowdury, & Diwadkar, 2019). Positive valence carries higher emotional salience presumably because the presentation of stimuli with positive valence activates latent representations of existing connections associated with positive life experiences (Lempert, Speer, Delgado, & Phelps, 2017;Pool, Brosch, Delplanque, & Sander, 2016;Reggev, Bein, & Maril, 2016).…”
Section: Comparison To Previous Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Normative studies of brain function In experimental contexts, both positive and negative valence hold substantial salience in the typical human brain and underpin brain networks that drive social interactions (Nummenmaa et al, 2012). However, whereas positively valenced stimuli are 'preferred' in healthy controls (Nielen et al, 2009;Winecoff et al, 2013), negatively valenced stimuli are more salient to patients with BPD (Soloff et al, 2015;Soloff, Chowdury, & Diwadkar, 2019). Positive valence carries higher emotional salience presumably because the presentation of stimuli with positive valence activates latent representations of existing connections associated with positive life experiences (Lempert, Speer, Delgado, & Phelps, 2017;Pool, Brosch, Delplanque, & Sander, 2016;Reggev, Bein, & Maril, 2016).…”
Section: Comparison To Previous Imaging Studiesmentioning
confidence: 99%
“…In this vein, the examination of other dimensional contributions including suicidality and childhood trauma (particularly sexual abuse) will be warranted in future investigations. We have shown that the lethality of suicidal attempts is related to fMRI responses to negative valenced stimuli used during sustained attention tasks (Soloff et al, 2019), consistent with altered fMRI profiles during self-reflection on aversive memories (Silvers et al, 2016). Childhood trauma (and particularly sexual abuse) is a known risk factor for BPD, with impacts particularly on medial temporal lobe structures such as the amygdala and hippocampus (Soloff, Nutche, Goradia, & Diwadkar, 2008), and also on brain network profiles during social cognition tasks (Duque-Alarcon, Alcala-Lozano, Gonzalez-Olvera, Garza-Villarreal, & Pellicer, 2019).…”
Section: Clinical 'Specificity'mentioning
confidence: 99%
“…BPD‐tb‐1, 119 BPD‐tb‐4, 122 BPD‐tb‐5, 123 BPD‐tb‐6, 124 and BPD‐tb‐9 125 demonstrated increased activity in the precuneus in response to varying negative stimuli. BPD‐tb‐7 126 also employed a negative (painful) stimulus and uncovered altered right supramarginal gyrus (rSMG) activity.…”
Section: Discussionmentioning
confidence: 96%
“…These findings highlight valence network emotion and feedback learning pathways that influence stable risk, proximal risk, and phenotypic expression. Other valence correlates of ideation (48, 49), attempt (50)(51)(52)(53)(54)(55), and attempt lethality (43,56,57) have also been reported.…”
Section: The Valence Network: Emotion Learning and Decision-making Biasesmentioning
confidence: 92%